BIAYA REKLAMASI DAN REVEGETASI LAHAN BEKAS TAMBANG BATUBARA - Hanis, Redha Nagara (ReTII, 2021)
Holders of Mining Permit situated in the forest area have to reclaim and revegetate the land where vegetation damaged by mining activities. Regulations have been made, including the Regulation No. P.04 / Menhut-II / 2011. Meanwhile, assessing the success of the forest reclamation activities has also been arranged through Regulation No. P.60 /Menhut-II/2009. In addition, there is the Indonesian Government Regulation No. 78 Year 2010 stating mining companies submit a sum of money as security for reclamation and post-mining. This research was conducted at PT. Karya Usaha Pertiwi and PT. Tanito Harum, Province of East Kalimantan. It aimed to assess the cost of reclamation and post-mining reclamation and post-mining activities with the assurance that had been submitted to the Government. Research methods include field research as well as interviews with several respondents from various stakeholders making and implementing policies related to reclamation and revegetation activities of ex-coal mines. The cost of reclamation and post-mining included direct costs and indirect costs. The research showed the cost of reclamation and post-mining plans PT. Karya Usaha Pertiwi was Rp 6,474,028,332 and PT Tanito Harum Rp 16,906,496,487. The benefits of research were to maximize the function of reclamation and post-mining reclamation guarantees in accordance with the planning of direct and indirect costs. East Kalimantan Provincial Local Government (Department of Energy and Mineral Resources) and Director General of Mineral and Coal, Ministry of Energy and Mineral Resources can provide oversight and guidance of conformity assurance and post-mining reclamation of mined land in order to create productive.